The Growth and Establishment of Floating Turions of Potamogeton crispus Are Not Favored by Summer Climate. Issue 3 (30th June 2014) - Xie, Dong; Zhou, Hengjie; Ji, Haiting; An, Shuqing
<x xml:space="preserve">Abstract</x> The dispersion of asexual propagules is an important determinant for the spread and establishment of many aquatic plant species. In order to improve the understanding of the expansion of the Potamogeton crispus population, an in situ growth experiment with P. crispus turions was performed in a 30 days period. The sinking turions produced longer seedlings and more leaves than that of floating turions during the experimental period. A lower dark respiration rate and higher activities of superoxide dismutase and peroxidase were detected in the floating turions than those in the sinking turions, indicating that the self‐protection process of the floating turions and stress condition (high sunlight exposure and temperature) in summer may influence the primary metabolites of these floating turions. Moreover, we also found that the scale leaf porosities of the floating turions would determine the buoyancy of turions. These results indicated that the sinking and floating of P. crispus turions are determined by the anatomical structures and in situ summer climatic condition is unfavorable for the establishment of P. crispus floating turions.